Strategi Guru dalam Menangani Siswa Disgrafia di Kelas VI SDN 26 Bukit Putus Dalam - Aulia Aftana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was motivated by the existence of students who experienced dysgraphia (difficulty writing). This difficulty in writing is one of the inhibiting factors in the learning process in class. So, based on this background, the aim of this research is to find out teachers' strategies for dealing with dysgraphia students in class VI at SDN 26 Bukit Putus Dalam. The approach used in this research is a qualitative approach with descriptive methods. Data collection techniques use observation and interviews. Data analysis uses the Milles and Huberman data analysis model. Test the validity of the data using data trigultion techniques. This research was conducted at SDN 26 Bukit Putus Dalam which is located in Linggo Sari Baganti District, Pesisir Selatan Regency, West Sumatra Province. The results of the research show that: the forms of writing difficulties experienced by class VI students at SDN 26 Bukit Putus Dalam consist of writing letters backwards, deleting and adding letters, and not reading fluently so they have difficulty writing. Then, that is the teacher's strategy in overcoming the writing difficulties of class VI students at SDN 26 Bukit Putus Dalam, namely by providing motivation to students by using interesting learning media, using appropriate learning methods, and using appropriate learning resources.